People’s View of Gandrung Dance Culture - Siti Shoimatul Azizah (Journal of Social, Culture, and Language, 2025)
The objectives of this study are, first, to examine the public's perspective. This aims to determine how the people of Jelun Village view gandrung, a traditional art form native to Banyuwangi Regency. Second, to examine the reasons why gandrung culture has not developed. This study uses a qualitative approach with field research. The location of this study is Jelun Village, Licin District, Banyuwangi Regency. This study uses a purposive technique, meaning data collection techniques are based on specific considerations. The informants in this study are considered to be the most knowledgeable and understanding of the research topic. Several factors indicate that Gandrung dance is no longer preserved. First, due to technological factors and a lack of interest from the community itself. Second, due to the fanaticism of the Jelun community, and women in the Jelun community are still very embarrassed to wear revealing clothing while dancing. Therefore, Gandrung dance here stems from the community's own unwillingness to preserve Gandrung dance.